The project work methodology in pre-school education: practice for children's development and learning - Ferreira, Carlos Alberto; Portilho, Flávia (Aprender, 2024)
This article is a report on the practice of the project work methodology with a group of pre-school children and a reflection on the lessons learnt at a cognitive level, but also in terms of attitudes and values. The aim is therefore to conceptualise and describe the teaching and learning practice of two projects - “The professions” and “The water” - and to reflect on their contribution to the children's development and learning. By carrying out these projects, the children developed autonomy and responsibility for carrying out tasks and learning together, as well as learning about professions and their roles and understanding the importance of saving water.
Keywords: project work; pre-school education; children; learnings